Changing practice using recovery‐focused care in acute mental health settings to reduce aggression: A qualitative study. (19th July 2018) - Lim, Eric; Wynaden, Dianne; Heslop, Karen
Abstract: Consumer aggression is common in acute mental health settings and can result in direct or vicarious psychological or physical impacts for both consumers and health professionals. Using recovery‐focused care, nurses can implement a range of strategies to reduce aggression and empower consumers to self‐regulate their behaviour, when faced with challenging situations, such as admission to the acute care setting. Currently, there is limited literature to direct nurses in the use of recovery‐focused care and how it can be used to reduce consumer aggression. Twenty‐seven mental health nurses participated in this study. The constructivist grounded theory method guided data collection and analysis to identify categories that accurately described participants' experiences. Five categories emerged that described how nurses can implement recovery‐focused care clinically to reduce the risk of consumer aggression: (i) identify the reason for the behaviour before responding; (ii) being sensitive to the consumer's trigger for aggression; (iii) focus on the consumer's strengths and support, not risks; (iv) being attentive to the consumer's needs; and (v) reconceptualize aggression as a learning opportunity. As the importance of promoting consumer recovery is now embedded in mental health policies internationally, nurses need to prioritize the application of recovery‐focused care clinically. Further research to provide evidence‐based outcomes supporting the use of recovery‐focused care is needed.